How Effective are the Order-to-Trade Ratio and Resting Time Regulations?. Issue 2 (31st August 2018) - Dalko, Viktoria; Wang, Michael H
ABSTRACT: The purpose of this paper is to assess the order-to-trade ratio (OTR) and resting time (RT) regulations that aim to contain order-based manipulative high-frequency trading (HFT). The paper examines the mechanism of limit order display and uses spoofing as one typical order-based manipulative scheme as the basis for assessment. The examination provides a theoretical foundation for the assessment of the OTR and RT regulations. The paper finds that order-based manipulation is the foundation of manipulative HFT tactics that take advantage of the incomplete display of limit order history by the stock exchange. Regarding deterrence of spoofing, the RT regulation is more effective than the OTR regulation, as the former creates uncertainty regarding spoof orders.